Ukrainian Poetic Sixties: Mykola Kholodnyi’s Creative Individuality - Urys, Tetiana (Respectus Philologicus, 2023)
The article is devoted to the little-studied Ukrainian poet of the sixties, dissident M. Kholodnyi, his creative style, analysis of motifs, images, and symbols of lyrical heritage, and the phenomenon of creative individuality. Socio-political reflection of Ukrainian tragedies, the role of the artist and his work singled out among the motifs of his poetry. There are images of famous Ukrainian writers who are carriers of the code of national memory and help to shape the national consciousness of future generations. A separate block constitutes his intimate lyric poetry reflecting the various facets of the spiritual and corporeal together with emotions ranging from romantic to deeply sensual. It is noted that among the writers of the 60s generation, his poetry is distinguished by the presence of sharp satire and tragedy in depicting paradoxical and absurd Soviet reality.